Euridice Giulia Caccinija - Kokole, Metoda (Keria (Ljubljana), 2012)
Euridice by Giulio Caccini was composed in 1600 on the libretto by Ottavio Rinuccini inspired by Ovid's and Virgil's classical mythological story about the divine singer Orpheus and his beloved Eurydice. The score was printed in the same year in Florence and was reprinted in 1615 in Venice. The opera is cast for eleven or twelve singers and it was apparently staged only once, in Florence in 1602. The presence of a copy of one of the earliest operas in the music history in Ljubljana by 1620 is a proof of a surprisingly early contact of the today's Slovenian territory with the then new operatic art.
Keywords: 1620; Caccini, Giulio; glasbene teme in motivi; Greek mythology; grška mitologija; Italian opera; italijanska opera; Ljubljana; Ljubljana (Slovenia); music themes and motives; partiture; scores